Bay-to-bay strategic alliances: the network linkages between Taiwan and the US venture capital industries [1]. (1st January 2002) - Saxenian, AnnaLee; Li, Chuen-Yueh
Taiwan stands out as an early success story in developing a venture capital (VC) industry. Domestic policy makers introduced VC in the early 1980s and today the island boasts a flourishing VC sector that is closely associated with the upgrading of the personal computer and integrated circuit industries. This paper describes the industry's origins in the close connections to Silicon Valley built by overseas Chinese, and it analyses the resulting patterns of cross-regional collaboration between the VC industries in the USA and Taiwan.